Investigating the Effectiveness of the RhythmoGame Method in Reducing Spelling Learning Disorders among First-Cycle Primary School Students - Saneie , Farzane; Mahor, Hossein; Shakiba , Abolghasem (Psychological Research in Individuals with Exceptional Needs, 2026)
The present study aimed to investigate the effectiveness of the RhythmoGame method in reducing spelling learning disorders among first-cycle primary school students. This study employed a quasi-experimental pretest–posttest design with an intervention group and a control group. The statistical population consisted of primary school students in Sabzevar, Iran, during the 2024–2025 academic year who had been identified as having spelling learning disorder. Thirty eligible students were assigned to the RhythmoGame intervention group and the control group, with 15 students in each group. Data were collected using the Wechsler Intelligence Scale for Children–Fourth Edition, the Colorado Learning Difficulties Questionnaire, and a researcher-developed spelling assessment measuring visual memory, visual sequential memory, auditory memory, auditory sensitivity, attention, educational spelling difficulties, and dysgraphia-related difficulties. The intervention group participated in the RhythmoGame program for two months, with two sessions per week lasting approximately 45–60 minutes. The program included rhythmic games, music, coordinated movement, auditory attention, sequencing, motor planning, response inhibition, and group interaction. The control group continued its usual educational activities. Data were analyzed using analysis of covariance after examining the relevant statistical assumptions. Analysis of covariance showed a statistically significant effect of group membership on posttest spelling learning disorder scores after controlling for pretest scores, F(1, 27) = 131.13, p < .001, partial η² = .829. The pretest covariate was also significant, F(1, 27) = 13.68, p = .001, partial η² = .336. The adjusted posttest results indicated that students in the RhythmoGame group had significantly lower spelling learning disorder scores than those in the control group. The findings indicate that RhythmoGame can be an effective complementary educational intervention for reducing spelling learning disorders in young primary school students, possibly through simultaneous engagement of auditory processing, attention, sequencing, memory, motor coordination, and response control.